Treatment of Sinonasal Adenocarcinoma: A Population-Based Prospective Cohort Study - König, Marton; Osnes, Terje; Bratland, Åse; Jebsen, Peter; Meling, Torstein R. (Journal of Neurological Surgery Part B: Skull Base, 2019)
Objectives Sinonasal adenocarcinoma (AC) is a potentially curable disease despite being an aggressive malignancy. Long-term survival can be achieved with early diagnosis and adequate multidisciplinary treatment. Our goal was to evaluate outcomes for patients with AC treated at our institution.Design In a population-based consecutive prospective cohort, we conducted an analysis of all patients treated for surface epithelial AC between 1995 and 2018.Results Twenty patients were included, and follow-up was 100%. The mean follow-up time was 89 months for the entire cohort (112 months for patients with no evidence of disease). Intestinal-type AC was found in 65%, whereas nonintestinal-type AC was found in 35% of all cases; 75% had stage T3/4 disease. Tumor grade was intermediate/high in 65%. Eighteen patients underwent treatment with curative intent (craniofacial resection [CFR] in 61%, transfacial approach in 39%, adjuvant radiotherapy in 89%), achieving negative margins in 56% of cases. Overall survival (OS) rates were 90, 68, and 54% after 2, 5, and 10 years of follow-up, respectively, and the corresponding disease-specific survival (DSS) rates were 90, 73, and 58%. Age over 60 years, tumor with a maxillary origin, and microscopic bone invasion were negative prognostic factors. Radical CFR was correlated with better OS and DSS.Conclusion The high probability of achieving radicality with CFR, the low complication rate, the acceptable toxicity of modern irradiation modalities, and the promising survival rates indicate that this strategy might be considered a safe and an effective option for treating patients with very advanced sinonasal AC.
Keywords: Sinonasal Adenocarcinoma; craniofacial resection; adjuvant radiotherapy; survival